Penggunaan Hidrolik Model Fisik Redesain Bendung Simongan - Niko Suhendra; Didik Kuswadi; Kelik Istanto (Jurusan Teknologi Pertanian, 2013)
Test model can provide a lot of possibilities of handling hydraulic problem as input for changes or improvements to the waterworks construction will be implemented. Therefore, physical modeling weir is the right step to knowing how to learn and cope with floods, good damage posed and a solution be handled. The purpose of this study was (1) Determine scale models and standard on many discharge meter prototype and (2) Perform the calibration test physical models contain. Implementation stages of this research started from the collection of data, software installation support, determination of scale models, model physical weir, the determination of the standard meter, test calibration model. Based on the results and discussion that have been described, it can be concluded with respect to the following: (1) Calculation of scale models produce mass-scale as follows: speed scale as large as 6,324; a 2.5 scale flow profile; and large scale Thomson 10119.289; (2) the completion of the process Curb Simongan done through physical modeling in the form of three-dimensional dam of five stages, namely Series 0, Series 1, Series 2, Series 3 and Series 4;(3) Calculation based on the Thomson High Level Discharge MeterÂ (m3/sec) prototype 200,500 m3/sec, m3/sec 700, and 850 consecutive m3/sec size of 37,445 cm, 45.522 cm, 49.314 cm and 51.746 cm; (4) The results of calibration test physical models of flow rate on debit Series 4 83 993 lt/sec indicates that the downstream flow velocity decreased after making 3 buildings that have elevation +3 m to the left and right downstream weir, elevation +4 m the middle of the downstream weir.Â Keywords: physical hidraulic model; redesign, weir simonganÂ